O ENSINO DE HISTÓRIA NOS COLÉGIOS MILITARES: ENTRE O LIVRO DIDÁTICO E EXPERIÊNCIAS DE ALUNOS E PROFESSORES - Soares, Felipe Bronoski (2016)
The aim of this study was to analyze the teaching and learning relationships in history subject in military schools having as reference two points: First, the textbook History of Empire of Brazil and Republic, a book especially designed for the Army Library to serve as educational tool to history lessons in military schools. Secondly the experiences and memories of students and teachers who have taught in units of the Military Schools System of Brazil. Besides understanding the textbook as a proper element of school culture (CHOPPAIN, 2002; JÚNIOR, 1997), the first chapter was intended to analyze the textbook History of Empire of Brazil and Republic from a similar criteria as the one established by the National Textbook Program (MIRANDA, DE LUCA, 2007). As a practical preparation, it was referred to chapters of the textbook History of Empire of Brazil and Republic toward a literature produced by the most recent historiography. The finding was that the textbook has several problems related to its conception of history, historiography choices and methodological construction in its entirety. The most obvious case is the approach about the period of the military regime whose narrative diverges significantly on the latest historiography. (CARDOSO, Lucileide, 2011; FICO, 2004; REIS, 2004; TOLEDO, 2004). The second time was building a web of relationships among people who actively participated in history classes in military schools. Theoretically it is analyzed how the production of oral sources (ALBERTI, 2004; FALCÃO, 2013; LAVERDI, 2013; PORTELLI, 1997; POZZI, 1997) contributed to the preparation of identification of social uses historical knowledge with reference to the concept of didactics of history (BERGMANN, 1990; CARDOSO, Oldimar, 2007; RÜSEN, 2006; SADDI, 2012). Finally, the interviews done with history teachers and students who have gone through units of the military schools revealed important aspects such actions and practices of resistance to military historiographical tradition; meanings of the everyday school activities full of rituals, festivities and public ceremonies; and intellectual understanding of teachers as representatives of the scientific discourse in conflict with the historic culture exposed in the book. Papers as Pacievicht (2007), Pimenta (1996), Rüsen (2010; 1994) were fundamental in this understanding. In addition to the results showed above, it is important to notice that the text presents both the theoretical and methodological analysis of the delimitation of the research study and the historicity of work as something fundamental to understand the characteristics, limits and real situations faced during the journey of its preparation.